SEDATIVE MEDICINES REGISTERED IN THE REPUBLIC OF UZBEKISTAN - Sidametova, Zaynab E. (International Journal of Psychosocial Rehabilitation, 2020)
Sedative medicines are generally used to treat diseases of the nervous system. The effect of sedatives is in the regulation of excitation processes and activation of inhibition in the brain. These medicines have moderate calming and antianxiety effects. They do not have any serious side effects, do not cause dependency and are the most frequently prescribed in the treatment of light neuroses. The analysis of the assortment of sedative medicines registered in the Republic of Uzbekistan showed that in the pharmaceutical market of Uzbekistan sedatives are presented in such dosage forms as tinctures, medicinal plant raw materials, syrups, capsules and tablets. The aim of the present work is to analyze the pharmaceutical market and the dosage forms of the sedative medicines, registered in Uzbekistan, CIS and foreign countries, so that to offer a new medication with sedative effect.Basing on the fact that the share of sedatives, registered in Uzbekistan in the form of syrups makes only 3 medications (from the number of domestic production), 1 medication (from the total number of production of CIS countries) and 5 medications (from the total number of foreign drugs), it is advisable to create a sedative medicine of plant origin in the form of a syrup. Materials and methods. For performing of the research work materials were used, given in “the State Register of medicines, medical products and medical equipment permitted for application in medical practice of the Republic of Uzbekistan” dated 2015-2019 (№ 19-23). [2-6]. Experimental part presents the analysis’s of the assortment of SMs (sedative medicines) registered in Uzbekistan, CIS and foreign countries, according to their dosage forms and using of content analysis of data on registration of the pharmacotherapeutic group (ATX Code - N05C).For providing accelerated development of the pharmaceutical industry and expansion of the domestic market with domestic medicines produced of local raw materials, a new medication on the base of "Phlegmen" sedative collection was offered for production. This sedative medicine was developed by the associates of the Tashkent Pharmaceutical Institute, successfully passed clinical tests and is produced in the Republic of Uzbekistan by SORB-TEH LLC, Uzbekistan.